FRI0438 POST-CHIKUNGUNYA CHRONIC ARTHRITIS - SHARING OF BANGLADESH EXPERIENCE OVER ONE YEAR FOLLOW UP OF 60 PATIENTS. (2nd June 2020) - Hossain, S.; Choudhury, M.; Islam, M. A.; Hassan, M. M.; Yeasmin, S.; Hossain, F.
Abstract : Background: Chikungunya virus (CHIKV) infection is an emerging disease which is responsible for several epidemics around the world 1 . Systematic review and meta-analysis had shown that approximately 25% of cases of Chikungunya(CHIK) would develop CHIK-Chronic Inflammatory Rheumatism and 14% would develop persistent arthritis (or spondylitis) 2 . Objectives: To describe the frequency of the clinical patterns of chronic arthritis & to characterize the clinical symptoms in a Bangladeshi cohort of CHIK patients 12months post-infection. Methods: In 2017, a Chikungunya outbreak occurred in Dhaka, Bangladesh, during which a prospective cohort of CHIK patients with confirmed diagnosis was constituted. A longitudinal follow up of 60 patients from an initial cohort of 142 patients, attending the out-patient department of Rheumatology, BSMMU, was done. Patients having arthritis/ arthralgia or both lasting more than 3 months were considered as chronic cases. Their baseline and follow-up symptoms at 3m, 6m and 12months were evaluated. Functional status was assessed with the Bengali Version Health Assessment Questionnaire (HAQ). Results: Of the initial 142 patients enrolled in the study, 135(95.1%) had CHIKV-IgM and 29(20.4%) had IgG positive. Patients that followed up in-person were predominantly adult (age 43.73 ± 11.09 years) and female 34 (56.7%). The majority of the patients 35 (58.3%) had undifferentiated arthritis. After three months, 8 (16.3%) had oligoarthralgia, 26 (53.1%) had polyarthralgia and 8 (16.3%) had polyarthralgia with oligoarthritis. At the end of one year, 13 (21.7%) patients underwent complete remission. Among the 47 patients, 21 had joint involvement where 11(52.4%) had polyarthralgia, 5(23.8%) had polyarthralgia with oligoarthritis, 5 (23%) had oligoarthralgia and 4 (19%) had monoarthralgia. Among the 47 patients, mild, moderate and severe functional disability was present in 89.4%, 6.4% and 4.3% patients respectively. Conclusion: After one year of follow up, one-third of the patients remained symptomatic. Polyarthralgia was the predominant clinical feature. Mild functional disability was also observed in a significant number of patients. References: [1]Ali Ou Alla S, Combe B. Arthritis after infection with Chikungunya virus. Best Pract Res Clin Rheumatol. 2011;25(3):337-46. [2]Rodríguez-Morales AJ et al. Prevalence of Post-Chikungunya Infection Chronic Inflammatory Arthritis: A Systematic Review and Meta-Analysis. Arthritis. Care. Res . 68(12), 1849-1858 (2016). Disclosure of Interests: None declared